INTERLEUKIN-10 PLASMA DAN LIMFOSIT-T CD4+ PENDERITA TERINFEKSI HIV - Kadek Mulyantari; Endang Retnowati; Nasronudin Nasronudin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
HIV & AIDS have become a global problem throughout the world including Indonesia. The incidence is rapidly increasing. Various treatment and efforts have been carried out but until now have not yet been succeeded, the mortality remains high. Examination of CD4+ lymphocyte-T which is carried out to determine the immune status and monitoring the treatment has some limitation. Besides the degradation of CD4+ lymphocyte-T, the increase of the disease progression is also followed by an increase of interleukin-10 as well. The determination of interleukin-10 is expected to be use as an alternative examination if CD4+ lymphocyte-T can not be performed. To analyze the correlation between the levels of plasma interleukin-10 and amount of CD4+ lymphocyte-T in the asymptomatic HIV infected patients. A cross sectional, observational analytical study of 41 patients with HIV infection stage I, has been conducted from March–April 2009, at the Intermediate Infectious Disease Care Unit Dr. Soetomo General Hospital, Surabaya. The diagnosis of HIV patients was based on positive result of HIV test using three (3) different methods. Eight mL venous blood were taken from each patient, 6 mL is put into a heparin tube for the examination of IL-10 plasma with ELISA method and 2 mL is put into a K3EDTA tube for examining the CD4+ lymphocyte-T using flowcytometry. The results showed of plasma IL-10 level and the amount of CD4+ lymphocyte-T, which were analyzed by Pearson correlation test to determine the correlation between the two (2) variabels. The IL-10 levels in HIV patients were 3.80–44.50 pg/mL (mean 18.09 pg/mL, SD 8.84 pg/mL). The amount of absolute CD4+ lymphocyte-T was 5–846 cells/µL (mean 322.07 cells/µL and SD 221.89 cells/µL), while the amount of percentage CD4+ lymphocyte-T was 0.41–29.48% (mean 13.99%, SD 7.62%). Statistical analyzes show a significant negative correlation either between plasma IL-10 level with absolute CD4+lymphocyte-T and plasma IL-10 level with percentage of CD4+ lymphocyte-T, e ach level of r was –0.652 and –0,683. A significant negative correlation was also formed between plasma IL-10 level and the amount of CD4+ lymphocyte-T in the HIV infected patients. In the HIV infected patients, the increase of plasma IL-10 level was followed by a decrease of CD4+ lymphocyte-T.